Konsep Teologi Pendidikan Islam Perspektif Ismail Raji Al-Faruqi - Nur Amalina Wafi' Azizah; Ikhsan Kamil Sahri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Science and education are an integration that cannot be separated, because knowledge has an impact on the world of education. The concept of education in Islam must continue to involve God in order to provide alternative answers to various problems in Islamic education. In theological studies, the main focus in education is based on the Al-Qur'an and Hadith. The purpose of this writing is to understand the theology of Islamic education and understanding the theology of the figure Ismail Raj'i al-Faruqi. Al-Faruqi himself, in his understanding, describes the global threat and Western imperialization culturally and then recommends to the Muslim generation to re-strengthen the basis of monotheism or theology. This research uses a qualitative method based on library research. Data collection uses literature in relevant books, journals and articles. The results of this research explain that al-Faruqi is determined to build a new, more Islamic scientific paradigm by utilizing modern scientific disciplines. From Ismail Raji Al-Faruqi's own thoughts, in explaining monotheism as the core of Islamic teachings, he tries to incorporate monotheism into all aspects of life so that life can proceed as a servant to Allah alone. Analysis of al-Faruqi with an Islamic approach through empirical modern thought with interpretive content. The knowledge system that will be built is a creative synthesis of two poles of knowledge, Western and Islamic.